Natural flavoring formulations of straw mushrooms and quality test with variations in temperature and drying time - SADLI SADLI; SITTI SALEHA; RAIYAN RAIYAN (Universitas Syiah Kuala, 2022)
Mushrooms contain a substance known as glutamic acid, that produce a savory taste which has the potential to be developed into a natural flavoring. The research began with the determination of amino acid levels in three phases of harvesting straw mushrooms, namely: the egg phase, the bud phase and the adult phase, by using High Performance Liquid Chromatography which aims to determine the harvesting phase with the highest glutamic acid content. The test results of amino acid levels showed the adult phase contained the highest glutamic acid levels of 49.08 mg/g. Furthermore, the manufacture of straw mushroom flour was performed with temperature variations of 60° C and 70° C and drying times of 6, 7 and 8 hours. Then the flavoring formulation was completed by mixing mushroom flour and other dry additives namely shallots, garlic, white pepper, tapioca flour, salt and sugar. The resulting flavoring test is conducted using a description test by assessing the sensory properties of natural flavorings, namely color, aroma, taste and texture. Based on a panelist rating, F2 (60°C, 7 hours) has the best score for color (3.88) and aroma (3.32). F5 (70°C, 7 hours) has the best score for taste (3.24) and F1 (60°C, 6 hours) has the best score for texture (2.08). The conclusion of this study is that mushrooms have a very high potential to be deformalized into natural flavorings, as well as the natural flavoring quality parameters of mushrooms is influenced significantly by temperature parameters and drying time